2003
DOI: 10.1097/01.tp.0000090753.99170.89
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cytochrome P450 3A5 genetic polymorphism on tacrolimus doses and concentration-to-dose ratio in renal transplant recipients1 2

Abstract: Determination of CYP3A5 genotype is predictive of the dose of tacrolimus in renal transplant recipients and may help to determine the initial daily dose needed by individual patients for adequate immunosuppression without excess nephrotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
170
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(196 citation statements)
references
References 10 publications
21
170
0
5
Order By: Relevance
“…Subjects homozygous for the variant * 3, likely owing to the lower metabolic drug clearance, require a lower tacrolimus dose to reach the desired therapeutic levels compared to the subjects with at least one * 1 copy who are considered to express the functional enzyme (21,40,41). Similar results have been previously reported for liver (8,(41)(42)(43), kidney (12,(44)(45)(46)(47), heart (48), and lung recipients (49). In particular, as regards to liver transplantation, our data support the primary importance of the donor with respect to the CYP3A5 genotype (8,43,(50)(51)(52)(53); however, they suggest a possible influence of the recipient genotype also (52), which might be corroborated by the known metabolic role of CYP3A5 in extra-hepatic tissues such as the intestine (51,53).…”
Section: Treated With Steroidssupporting
confidence: 81%
“…Subjects homozygous for the variant * 3, likely owing to the lower metabolic drug clearance, require a lower tacrolimus dose to reach the desired therapeutic levels compared to the subjects with at least one * 1 copy who are considered to express the functional enzyme (21,40,41). Similar results have been previously reported for liver (8,(41)(42)(43), kidney (12,(44)(45)(46)(47), heart (48), and lung recipients (49). In particular, as regards to liver transplantation, our data support the primary importance of the donor with respect to the CYP3A5 genotype (8,43,(50)(51)(52)(53); however, they suggest a possible influence of the recipient genotype also (52), which might be corroborated by the known metabolic role of CYP3A5 in extra-hepatic tissues such as the intestine (51,53).…”
Section: Treated With Steroidssupporting
confidence: 81%
“…However, in renal transplant patients, the in vivo clearance of both tacrolimus and sirolimus is dependent on CYP 3A5 polymorphism: it was demonstrated that patients with the CYP 3A5*3/*3 genotype had significantly lower tacrolimus dose-adjusted trough level than CYP 3A5*1 allele carriers (Hesselink et al, 2003;Thervet et al, 2003). Anglicheau et al (2005) found a significant association between the CYP 3A5*3 single nucleotide polymorphism and sirolimus doseadjusted trough levels in 69 patients under a sirolimus-based rescue therapy, but not in 51 de novo patients or in 29 patients coadministered cyclosporine or tacrolimus (Anglicheau et al, 2005).…”
Section: Metabolism Of Sirolimus By Cyp 3a4 and Cyp 3a5mentioning
confidence: 99%
“…Such results have been reported previously in the literature concerning this polymorphism. [5][6][7][8][9][10] A previous study by Patel and associates studied the effect of CYP3A5 polymorphism on tacrolimus drug dosing in North Indian renal allograft recipients. 11 To our knowledge, the present study is the first study to show the association between CYP3A5 genetic polymorphism and tacrolimus drug level in a South Indian population.…”
Section: Discussionmentioning
confidence: 99%